Approach to Epistaxis - Raisa Chowdhury; Sena Turkdogan; Jennifer A. Silver; Jessica Hier; Stuart Bursey; Danah Quttaineh; Mark Khoury; Lamiae Himdi (Journal of Otorhinolaryngology, Hearing and Balance Medicine)
Epistaxis, commonly referred to as nosebleeds, is a frequent clinical presentation with etiologies spanning from localized trauma to systemic conditions and medication effects. Despite its high prevalence, management approaches vary significantly depending on the cause and severity. To provide a comprehensive review of current management strategies for epistaxis, focusing on initial interventions, evaluation techniques, and preventive measures. A structured review of the literature was conducted to identify effective strategies for the initial management, evaluation, and prevention of epistaxis. Emphasis was placed on practical applications for clinicians in both emergency and outpatient settings. Initial Management: Direct pressure and topical vasoconstrictors remain the first-line interventions. Persistent cases may require nasal packing or cautery. Evaluation: Identification of underlying causes such as hypertension, coagulopathies, and structural nasal abnormalities is crucial, particularly in recurrent or severe cases. Laboratory tests and imaging may aid in diagnosis and management planning. Prevention: Patient education on nasal hygiene, avoidance of nasal trauma, and maintenance of a humidified environment are critical in reducing recurrence. Integrating effective initial management with thorough evaluation and preventive strategies significantly improves patient outcomes.